Biofragmentation of Polystyrene Microplastics: A Silent Process Performed by Chironomus sancticaroli Larvae - Queiroz, Lucas G.; Prado, Caio C. A.; Melo, Eduardo C.; Moraes, Beatriz R.; de Oliveira, Paulo F. M.; Ando, Rômulo A.; Paiva, Teresa C. B.; Pompêo, Marcelo; Rani-Borges, Bárbara [UNESP] (American Chemical Society (ACS), 2024)
Polystyrene (PS) is one of the main synthetic polymers produced around the world, and it is present in the composition of a wide variety of single-use objects. When released into the environment, these materials are degraded by environmental factors, resulting in microplastics. We investigated the ability of Chironomus sancticaroli (Diptera, Chironomidae) to promote the fragmentation of PS microspheres (24.5 ± 2.9 μm) and the toxic effects associated with exposure to this polymer. C. sancticaroli larvae were exposed to 3 different concentrations of PS (67.5, 135, and 270 particles g-1 of dry sediment) for 144 h. Significant lethality was observed only at the highest concentration. A significant reduction in PS particle size as well as evidence of deterioration on the surface of the spheres, such as grooves and cracks, was observed. In addition, changes in oxidative stress biomarkers (SOD, CAT, MDA, and GST) were also observed. This is the first study to report the ability of Chironomus sp. to promote the biofragmentation of microplastics. The information obtained demonstrates that the macroinvertebrate community can play a key role in the degradation of plastic particles present in the sediment of freshwater environments and can also be threatened by such particle pollution.
Keywords: biological fragmentation; macroinvertebrate; oxidative stress; polystyrene